Development of electrospun multifunctional fibrous structures for icephobic and superhydrophobic applications - Tas, Mahmut (2022)
Icephobicity is defined as the ability of a solid surface to prevent ice accumulation or the potential of repelling ice from the surface. On the other hand, superhydrophobicity is a physical property of a surface, which means lacking affinity for water, and tending to repel water. Although these two surface properties have critical application areas such as energy harvesting systems, transportation, corrosion resistance coatings and friction reduction, fabricating superhydrophobic and icephobic surfaces is still a big challenge due to the lack of scalable, straightforward, and cost-effective production methods. Moreover, integrating additional functions, including electromagnetic interference (EMI) shielding and electrical conductivity to these materials to achieve multifunctionality, enables many modern applications, such as EMI shielding protective devices and power transmission systems.